Respuesta :
The equation of the function would be:
B. f(x)=4x+4, because if x=2, and if the answer is 12, 12 divided by 2 is 6, so f=6 4 multiplied by 2 is 8 added by 4 is 12. The equation in numbers would be 6(2)=12 or 6(2)=4(2)+4 which ends up being 12=12.
B. f(x)=4x+4, because if x=2, and if the answer is 12, 12 divided by 2 is 6, so f=6 4 multiplied by 2 is 8 added by 4 is 12. The equation in numbers would be 6(2)=12 or 6(2)=4(2)+4 which ends up being 12=12.
Step-by-step explanation:
We are given that:
f(2)=12
We have to determine which could be the equation of the function.
i.e. the function which satisfies f(2)=12
A. f(x) = 8x – 2
f(2)=8×2-2
f(2)=14
B. f(x) = 4x + 4
f(2)=4×2+4
f(2)=12
C. f(x) = 6x – 4
f(2)=6×2-4
f(2)=8
D. f(x) = –4x – 4
f(2)= -4×2-4
f(2)= -12
Hence, given f(2) = 12, equation of the function could be:
B. f(x) = 4x + 4